2024
DOI: 10.1017/pen.2023.13
|View full text |Cite
|
Sign up to set email alerts
|

Whither dominance? An enduring evolutionary legacy of primate sociality

Drew M. Altschul

Abstract: This article discusses dominance personality dimensions found in primates, particularly in the great apes, and how they compare to dominance in humans. Dominance traits are seen in virtually all primate species, and these dimensions reflect how adept an individual is at ascending within a social hierarchy. Among great apes, dominance is one of the most prominent personality factors but, in humans, dominance is usually modeled as a facet of extraversion. Social, cultural, and cognitive differences between human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…They argue from the primate data that discrepancies in human research would be resolved with more broad ranging and nuanced analysis. Consistent with this, Altschul ( 2024 , §1.3) treats dominance as multifaceted, being essentially similar across primates but with a drift of its facets during hominid evolution so that they now each align more with separate traits than with a single dominance factor. Somewhat reminiscent of the rat work with artificially selected strains, Hopkins et al ( 2023 , §1.4) analyzed natural variation in attention skills (using a similar task to human testing) in a large (N = 189) cohort of chimpanzees ( Pan troglodytes ) and concluded that low versus high scorers provide “an excellent model for understanding the mechanisms underlying social impairment related to [Autism Spectrum Disorder].” Critically, they obtained Big 5 personality scores from carer ratings and gray matter volume from MRI – finding involvement of extraversion and of the social brain network.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…They argue from the primate data that discrepancies in human research would be resolved with more broad ranging and nuanced analysis. Consistent with this, Altschul ( 2024 , §1.3) treats dominance as multifaceted, being essentially similar across primates but with a drift of its facets during hominid evolution so that they now each align more with separate traits than with a single dominance factor. Somewhat reminiscent of the rat work with artificially selected strains, Hopkins et al ( 2023 , §1.4) analyzed natural variation in attention skills (using a similar task to human testing) in a large (N = 189) cohort of chimpanzees ( Pan troglodytes ) and concluded that low versus high scorers provide “an excellent model for understanding the mechanisms underlying social impairment related to [Autism Spectrum Disorder].” Critically, they obtained Big 5 personality scores from carer ratings and gray matter volume from MRI – finding involvement of extraversion and of the social brain network.…”
Section: Discussionmentioning
confidence: 96%
“…… Dominance itself can be subdivided into correlated subfactors: domineering, prestige, and leadership. Various explanations have been posed for why dominance has declined in prominence within human personality factor structures.” (Altschul, 2024 )…”
Section: Observation: Personality In Non-human Primatesmentioning
confidence: 99%
See 3 more Smart Citations